A large-scale, prospective, observational study of leukocytapheresis for ulcerative colitis: Treatment outcomes of 847 patients in clinical practice. (1st September 2014) - Yokoyama, Yoko; Matsuoka, Katsuyoshi; Kobayashi, Taku; Sawada, Koji; Fujiyoshi, Tateshi; Ando, Takafumi; Ohnishi, Yoshifumi; Ishida, Tetsuya; Oka, Masashi; Yamada, Masahiro; Nakamura, Takashi; Ino, Tomoko; et al.
Abstract: Background and aims: Leukocytapheresis is an extracorporeal therapy for ulcerative colitis. However, no large-scale study on leukocytapheresis has been reported. This large-scale, prospective, observational study aimed to evaluate the treatment outcomes of leukocytapheresis for active ulcerative colitis in clinical practice. Methods: Patients with active ulcerative colitis treated with leukocytapheresis using a Cellsorba E column between May 2010 and December 2012 were enrolled from 116 medical facilities in Japan. Results: A total of 847 patients were enrolled, and 623 were available for efficacy analysis. Out of 847 patients, 80.3% of the patients had moderate to severe disease activity, and 67.6% were steroid refractory. As concomitant medications, 5-aminosalicylic acids, corticosteroids, and thiopurines were administered to 94.8%, 63.8%, and 32.8% of the patients, respectively. In addition, infliximab and tacrolimus were concomitantly used in 5.8% and 12.3%, respectively. Intensive leukocytapheresis (≥ 4 leukocytapheresis sessions within the first 2 weeks) was used in > 70% of the patients. Adverse events were seen in 10.3% (87/847), which were severe in only 5 patients (0.6%). Any concomitant medications did not increase the incidence of adverse events. Intensive leukocytapheresis was as safe as the conventional weekly procedure. The overall clinical remission rate was 68.9% (429/623), and the mucosal healing rate was 62.5% (145/232). Clinical remission was achieved more frequently and rapidly in the intensive group than in the weekly group. Conclusions: This large-scale study indicates that leukocytapheresis, including intensive procedure, is a safe and effective therapeutic option for active ulcerative colitis.